Pulmonary vasodilator use in continuous-flow left ventricular assist device management - Pirlamarla, Preethi (Ann Transl Med, 2021)
Pulmonary hypertension (PH) due to left heart disease is the most common etiology for PH. PH in patients with heart failure with reduced fraction (HFrEF) is associated with reduced functional capacity and increased mortality. PH-HFrEF can be isolated post-capillary or combined pre- and post-capillary PH. Chronic elevation of left-sided filling pressures may lead to reverse remodeling of the pulmonary vasculature with development of precapillary component of PH. Untreated PH in patients with HFrEF results in predominant right heart failure (RHF) with irreversible end-organ dysfunction. Management of PH-HFrEF includes diuretics, vasodilators like angiotensin-converting enzyme inhibitors or angiotensin-receptor blockers or angiotensin-receptor blocker-neprilysin inhibitors, hydralazine and nitrates. There is no role for pulmonary vasodilator use in patients with PH-HFrEF due to increased mortality in clinical trials. In patients with end-stage HFrEF and fixed PH unresponsive to vasodilator challenge, implantation of continuous-flow left ventricular assist device (cfLVAD) results in marked improvement in pulmonary artery pressures within 6 months due to left ventricular (LV) mechanical unloading. The role of pulmonary vasodilators in management of precapillary component of PH after cfLVAD is not well-defined. The purpose of this review is to discuss the pharmacologic management of PH after cfLVAD implantation.